2012
DOI: 10.1111/j.1748-1716.2012.02438.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological characterization of sodium‐activated potassium channels in NG108‐15 and NSC‐34 motor neuron‐like cells

Abstract: There is a direct association of Na(+) and K(Na) channels which can provide the rapid activation of K(Na) channels required to regulate AP firing occurring in motor neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
2
14
0
4
Order By: Relevance
“…Δ G 0 for I K(DR) activation at 0 mV with or without treatment of SGX would be equal to q  ×  F  ×  V 1/2 [25, 26]. The standard errors of Δ G 0 (i.e., ) were calculated according to:where σ q and represent the standard errors in q and V 1/2 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Δ G 0 for I K(DR) activation at 0 mV with or without treatment of SGX would be equal to q  ×  F  ×  V 1/2 [25, 26]. The standard errors of Δ G 0 (i.e., ) were calculated according to:where σ q and represent the standard errors in q and V 1/2 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, in our study, neither tetrodotoxin, ranolazine nor riluzole was demonstrated to have any effects on PALCAR-stimulated I MEP in GH 3 cells. Those compounds are recognized to suppress the amplitude of late Na + currents [32,33]. PALCAR produced a progressive increase of I MEP in GH 3 cells with an EC 50 value of 2.4 µM.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate set of experiments, the pipette was filled with the solution which contained chlorotoxin (1 µM). By use of F-250 fluorescence spectrophotometer and the ratiometric fura-2 measurement, the free Ca 2+ concentration for high K + -bathing solution was 208±17 nM (n=7 Cell preparation and differentiation NSC-34 neuronal cells were originally produced by fusion of the motor neuron-enriched, embryonic mouse spinal cords with the mouse neuroblastoma [14,21]. These cells were kindly provided by Professor Dr. Yuh-Jyh Jong (Department of Pediatrics, Kaohsiung Medical University Hospital, Kaohsiung City, Taiwan).…”
Section: Drugs and Solutionsmentioning
confidence: 99%
“…An anti-vibration air table was used to enhance stability during electrophysiological recordings. Patchclamp recordings were obtained in cell-attached, inside-out, or whole-cell configuration using either an RK-400 (Biol-Logic, Claix, France) or Axopatch 200B (Molecular Devices, Sunnyvale, CA) amplifier [21,22]. The junctional potentials between the pipette solution and extracellular medium were corrected immediately before seal formation was made.…”
Section: Electrophysiological Measurementsmentioning
confidence: 99%